HARMONISASI HUBUNGAN ETNIK MELAYU, DAYAK DAN CINA DALAM MASYARAKAT MULTIKULTURAL DI KOTA PONTIANAK PROVINSI KALIMANTAN BARAT - Lukman Jafar (Indonesian Journal of Dialectics, 2012)
In cultural interaction, social integration occurs among ethnics or tribe that is shown by social bound that strengthen the ralation among them. In those interaction respect, believe,and solidarity, appeared to keep peaceful among each other. However, cultural interaction may ruin social integration also. This may couse hostility, prejudice, insecurity, and conflict among the ethnics.This study used qualitative approach to research the ethnics harmonization. The data was collected from observation and interview of community leaders, tribes leaders, common people in societies, non government organization and local government leader. Social prejudice, stereotype and ethnocentrism influenced by family, environment and personal experience causes some ethnics reluctant to communicate with another ethnics. The ethnics of Malay, Dayak, and Chinese have it is own cultural wisdom from their religion and traditional values. The ethnical diffrences is not the barrier of inter ethnics interaction; The intensity of interaction occurs on social activity, bussines, and religiosity become the channel to cultural understanding so that tolerancy could overcome the border of culture.